Multi-omics analysis provides new insights into the changes of important nutrients and fructose metabolism in loquat bud sport mutant - Song, Hai-yan; Zhao, Ke; Pei, Yan-Gang; Chen, Hong-xu; Wang, Xiao-an; Jiang, Guo-Liang; Xie, Hong-Jiang; Chen, Dong; Gong, Rong-gao (Frontiers in Plant Science, 2024)
Bud sport is a common and stable somatic variation in perennial fruit trees, and often leads to significant modification of fruit traits and affects the breeding value. Here, we conducted a multi-omics analysis of loquat fruits at different developmental stages of a white-fleshed bud sport mutant of Dongting loquat (TBW) and its wild type (TBY). The findings from the detection of main fruit quality indices and metabolites suggested that bud sport resulted in a reduction in the accumulation of carotenoids, fructose, titratable acid and terpenoids at the mature stage of TBW, while leading to the accumulation of flavonoids, phenolic acids, amino acids and lipids. The comparably low content of titratable acid further enhances the balanced and pleasent taste profile of TBW. Expression patterns of differentially expressed genes involved in fructose metabolism exhibited a significant increase in the expression level of S6PDH (EVM0006243, EVM0044405) prior to fruit maturation. The comparison of protein sequences and promoter region of S6PDH between TBY and TBW revealed no structural variations that would impact gene function or expression, indicating that transcription factors may be responsible for the rapid up-regulation of S6PDH before maturation. Furthermore, correlation analysis helped to construct a comprehensive regulatory network of fructose metabolism in loquat, including 23 transcription factors, six structural genes, and nine saccharides. Based on the regulatory network and existing studies, it could be inferred that transcription factors such as ERF, NAC, MYB, GRAS, and bZIP may promote fructose accumulation in loquat flesh by positively regulating S6PDH. These findings improve our understanding of the nutritional value and breeding potential of white-fleshed loquat bud sport mutant, as well as serve as a foundation for exploring the genes and transcription factors that regulate fructose metabolism in loquat.